A grounded theory exploration of the enablers and barriers of public healthcare access for people with comorbid serious mental and chronic physical illnesses in Jamaica. - Patrice Whitehorne-Smith; Kunal Lalwani; Robyn Martin; Gabrielle Mitchell; Ben Milbourn; Wendel Abel; Sharyn Burns (PLoS ONE, 2024)
Chronic physical illnesses (CPI) are highly prevalent among people with serious mental illnesses (PWSMI) yet people in this population experience significant challenges accessing healthcare. This study utilised a constructivist grounded theory approach to collect and analyse data related to the enablers and barriers to public healthcare access for PWSMI & CPI. Data were collected through semi-structured interviews conducted with fifty-seven participants comprising PWSMI &CPI and their caregivers, health policymakers, primary care physicians, psychiatrists, and mental health nurses. Enablers and barriers to healthcare access were represented using a socio-ecological model consisting of five levels: wider society, health system, clinician, family and community, and individual. Jamaica's free public healthcare system was the most pronounced enabler of healthcare access, while poverty, stigma, and discrimination were the most pronounced barriers. Factors such as social support, time, clinician beliefs, attitudes and training, and individual characteristics were identified as consisting of dimensions that were both enablers and barriers to healthcare access. These findings indicated that factors that influenced healthcare access for PWSMI & CPI were aligned with the social determinants of health. Improved healthcare access for PWSMI & CPI necessitates strategies that incorporate a multi-sectoral approach to address social and environmental factors influencing healthcare access across all levels of the socio-ecological model.